Body Dissatisfaction Ditinjau dari Social Comparison pada Perempuan Dewasa Awal di Kabupaten Karawang - Rachmat, Andieny Putri; Riza, Wina Lova; Aisha, Dinda (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2024)
Body dissatisfaction is an individual's assessment of his or her body shape, which involves comparing the perception of his or her body image with other individuals, excessive views of his or her body image, individual understanding of his or her body shape, and significant changes in his or her body shape. The purpose of this study was to determine the effect of social comparison on body dissatisfaction in early adult women in Karawang Regency. The method used in this research is quantitative method. The population in this study were early adult women with an age range of 18-25 years who live in Karawang Regency. The sampling technique in this study used accidental sampling technique, and the number of respondents in this study was 280 respondents. The measuring instrument in this study for the social comparison scale uses the Physical Appearance Comparison Scale-Revised (PACS-R) scale and for the body dissatisfaction scale using the Body Shape Questionnare-34 (BSQ-34) scale. The data analysis techniques used in this study are normality test, linearity test, simple linear regression hypothesis test, and additional tests, namely the coefficient of determination test and categorization test. Based on the results of the research that has been conducted, the results show that the significance value is 0.000 <0.05, and it can be concluded that there is an influence of social comparison on body dissatisfaction in early adult women in Karawang Regency. The results of the coefficient of determination test with an R square value of 0.719, which means that the amount of influence of social comparison on body dissatisfaction is 71.9%.